The prevalence and determinants of social anxiety disorder among people living with HIV/AIDS in Southwestern Ethiopia: a cross-sectional study - Alemayehu, Yadeta; Adem Hussen, Mustefa; Abdu, Zakir; Dule, Aman; Hajure, Mohammedamin; Mulatu, Gebremeskel; Gezimu, Wubishet; Alemu, Solomon Seyife; Wedajo, Lema Fikadu (Frontiers in Psychiatry, 2024)
Background: Social anxiety disorder imposes impacts of functional disability, poor educational achievement, loss of work productivity, social impairment, greater financial dependency, and impairment in quality of life. Therefore, the aim of this study was to assess the prevalence and identify determinants of social anxiety disoder among peoples living with HIV/AIDS. Methods: A cross-sectional study was conducted from May 1–30, 2022, among sampled 354 peoples living with HIV using a simple random sampling technique. Social Phobia Inventary (SPIN) Scale was used to assess the presence of social anxiety disorder. Data were gathered using chart review tools and a structured questionnaire which was given by a pretested face-to-face interviewer. SPSS version 25 was used to analyze the data once it was imported into EpiData Manager version 4.6. Both binary and multivariable logistic regressions were performed. After calculating odds ratios with a 95% confidence interval, statistical significance was established at p < 0.05. Results: About 336 respondents participated in the study, making a response rate of 94.91%. The magnitude of social anxiety disorder was 32.44% (95% CI: 27.4, 37.2). Being female (AOR = 3.55, 95% CI: 1.61, 7.84), having stage III/IV HIV/AIDS status (AOR = 3.17, 95% CI: 1.10, 9.13), being alcohol dependent (AOR = 2.81, 95% CI: 1.45, 5.44), and having perceived stigma (AOR = 5.62, 95% CI: 2.95, 10.72) were predictors of social anxiety disorder. Conclusion: In this study, about one third of peoples living with HIV/AIDS had social anxiety disorder. Being female, having stage III/IV HIV/AIDS status, being alcohol dependent and having perceived stigma were predictors of social anxiety disorder. Therefore, training of health care provider on screening, counseling and management of social anxiety disorder is important.